The Relation between Obesity and Survival after Surgical Resection of Hepatitis C Virus-Related Hepatocellular Carcinoma - Hiroki Nishikawa; Akira Arimoto; Tomoko Wakasa; Ryuichi Kita; Toru Kimura; Yukio Osaki (Gastroenterology Research and Practice)
Background and Aims. We aimed to investigate the relationship between obesity and survival in hepatitis C virus-(HCV-) related hepatocellular carcinoma (HCC) patients who underwent curative surgical resection (SR). Methods. A total of 233 patients with HCV-related HCC who underwent curative SR were included. They included 60 patients (25.8%) with a body mass index (BMI) of > 25 kg/m2 (obesity group) and 173 patients with a BMI of < 25 kg/m2 (control group). Overall survival (OS) and recurrence-free survival (RFS) rates were compared. Results. The median follow-up periods were 3.6 years in the obesity group and 3.1 years in the control group. The 1-, 3-, and 5-year cumulative OS rates were 98.3%, 81.0%, and 63.9% in the obesity group and 90.0%, 70.5%, and 50.3% in the control group (). The corresponding RFS rates were 70.1%, 27.0%, and 12.0% in the obesity group and 70.1%, 39.0%, and 21.7% in the control group (). There were no significant differences between the obesity group and the control group in terms of blood loss during surgery () and surgery-related serious adverse events (). Conclusions. Obesity itself did not affect survival in patients with HCV-related HCC after curative SR.